2014
DOI: 10.1111/acer.12403
|View full text |Cite
|
Sign up to set email alerts
|

A Surveillance Tool Using Mobile Phone Short Message Service to Reduce Alcohol Consumption Among Alcohol-Dependent Patients

Abstract: In detoxified alcohol-dependent patients, relapse prevention based on SMS was well received and implemented efficiently and rapidly. An adequately powered multicenter study is currently being conducted to test the nonsignificant but encouraging findings of this exploratory study with more rigorous trial methods (ISRCTN78350716).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(86 citation statements)
references
References 41 publications
1
81
1
3
Order By: Relevance
“…Several recent studies have shown that mobile phone‐delivered interventions have the potential to influence drinking behaviour in emergency department attendees 16, 17, 18, college students 19, 20, young people 21, adults 22 and alcohol‐dependent patients 23. Delivering an alcohol brief intervention by mobile phone would be ideal for targeting disadvantaged groups who may be reluctant to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that mobile phone‐delivered interventions have the potential to influence drinking behaviour in emergency department attendees 16, 17, 18, college students 19, 20, young people 21, adults 22 and alcohol‐dependent patients 23. Delivering an alcohol brief intervention by mobile phone would be ideal for targeting disadvantaged groups who may be reluctant to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…The participants received additional support feedback in response to about a third of their messages. The shortest intervention was two weeks in duration [51]. The intensity was also very high in this intervention; on average the participants received 8 and sent 4 messages each day.…”
Section: Intensity and Duration Of The Interventionsmentioning
confidence: 97%
“…were a text messaging system [34,35], an integrated online counseling intervention [37], a computerized intervention for anger management (Cougle et al, 2017), integrated text messaging systems that included online counseling [49][50][51], a text messaging intervention that included medication monitoring and support [82], and a GPS based app designed to predict the location of heroin craving [52]. Three studies focused on alcohol only, while four addressed mixed or poly substance use.…”
Section: Intervention Effects On Substance Use Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[60,61] For example, Lucht showed that twice weekly phone prompts increased phone based counseling sessions in alcohol dependent patients. [60] To increase the likelihood that SPCM group participants will use the resources available through the app, the phone will be programmed to automatically prompt/suggest a connection with their case manager twice per week. Specifically, the phone will ring/vibrate on two occasions each week at random times between 9:00 am and 5:00 pm, Monday through Friday, to ask participants if they would like to contact their case manager.…”
Section: Study Conditionsmentioning
confidence: 99%